The Effects of Transformational and Transactional Leadership on Individual Creative Performance: Role of Follower's Motivation, Identity and Self-esteem - Kuzmenko, Tetyana (My University, 2009)
Leadership behaviors play an important role in followers' performance. In today's competitive world, organizations gain advantage from creativity of their employees. Yet, there has been little research done on the effects of transformational and transactional leadership on followers' creative performance. The present study investigates the relationships between the components of transformational leadership (charisma, intellectual stimulation, and individualized consideration), transactional leadership (e.g. contingent reward behavior) and followers' creative performance. The proposed model examines the role of followers' intrinsic motivation, self-esteem and identity (e.g. personal and collective) in these relationships. While the study's hypotheses were not supported, charisma (β = .39, ρ < .01) and transactional leadership (β = .36, ρ < .05) positively predicted creativity in the absence of any controls. The effect of charisma was not consistent with expectations, though that associated with transactional leadership was.
Keywords: business, leadership, creative performance, follower